2016
DOI: 10.1038/hdy.2016.27
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in nitrogen fixation capacity could be part of the domestication process in soybean

Abstract: Biological nitrogen fixation (BNF) in soybeans is a complex process involving the interplay between the plant host and the symbiotic rhizobia. As nitrogen supply has a crucial role in growth and development, higher nitrogen fixation capacity would be important to achieve bigger plants and larger seeds, which were important selection criteria during plant domestication by humans. To test this hypothesis, we monitored the nitrogen fixation-related performance in 31 cultivated and 17 wild soybeans after inoculati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
5
40
1
Order By: Relevance
“…Moreover, the fast development of the metaxylem duct undoubtedly contributes to the transportation of substances, and the thickening of the cell walls of these structures improves the support function of the roots. Soybean roots contain bacteria in the nodule for nitrogen fixation, which is apart from conduction or support (Munoz et al, 2016). In our results, as compared to the wild soybeans, the cultivated soybeans essentially exhibited a decreasing trend in the protein expression levels in their root tips.…”
Section: Discussionsupporting
confidence: 61%
“…Moreover, the fast development of the metaxylem duct undoubtedly contributes to the transportation of substances, and the thickening of the cell walls of these structures improves the support function of the roots. Soybean roots contain bacteria in the nodule for nitrogen fixation, which is apart from conduction or support (Munoz et al, 2016). In our results, as compared to the wild soybeans, the cultivated soybeans essentially exhibited a decreasing trend in the protein expression levels in their root tips.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, the position of QNN17-2 identified on Gm17 overlapped with findings from another study, which strongly indicated that this QTL might be associated with nodule traits and NopB. A QTL localized on Gm17 was detected by using a RI population inoculated with USDA110, which was identified from total ureides commonly used as parameters to measure nitrogen fixation (Muñoz et al, 2016). We only detected one QTL localized on Gm10 called QNDW10-1, which was not found in previous research.…”
Section: Discussionsupporting
confidence: 60%
“…However, the positions of QNN17‐1 and QNN17‐2 were located close to each other. Moreover, a QTL was identified on chromosome 17 for total ureides using a recombinant inbred (RI) population inoculated with USDA110 (Muñoz et al, ) whose position overlapped with QNN17‐2 . In addition, only one QTL for NDW was identified after inoculation with the HH103Ω nopB mutant.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-two soybean lines of different maturity groups (II-IX) and genetic backgrounds were selected for this study based on their potential N 2 fixation, nodulation, and higher yield in order to investigate the association of growth stages and N 2 fixation (Table 1). Additionally, three checks were included; the nonnodulating soybean cultivars Nitrasoy (Burton, Israel, & Bishop, 2006) and D68-099 (Hartwig, 1994) for estimating the amount of N derived from fixation as well as the supernodulating mutant SS2-2 (Youn et al, 2008;Youn et al, 2009) for evaluating the levels of N 2 fixation.…”
Section: Plant Materialsmentioning
confidence: 99%